Bronislaw Baczko (1924-2024) - Andrea Marchili; Michel Porret; Gabriella Silvestrini (Scienza & Politica)
The centenary of Bronislaw Baczko’s birth provides an opportunity to reflect again on the nature of modernity, focusing on the relationship between Enlightenment, revolution and democracy.